1987
DOI: 10.1128/jcm.25.5.889-892.1987
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-1 in augmenting serum neutralization of bacterial lipopolysaccharide

Abstract: We have previously described an assay to quantify the serum neutralization of bacterial lipopolysaccharide which is based on a spectrophotometric Limulus amoebocyte lysate test (T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…These proteins could inhibit the synthesis or neutralize the action of mediators involved in the genesis of fever, and the treatment with galactosamine, simultaneously with the first injection of MDP or endotoxin, would inhibit their synthesis and consequently the development of pyrogenic tolerance. In support of this hypothesis, it has been proposed that a seric component, probably of hepatic origin, neutralizes endotoxin (29,41) and that serum with a high concentration of APP reduces the lethality induced by endotoxin (38). Directly related to the phenomenon investigated in the present study, it has been demonstrated that serum amyloid A, an APP produced by the liver, inhibits fever and hypothalamic production of prostaglandin E 2 induced by cytokines in mice (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins could inhibit the synthesis or neutralize the action of mediators involved in the genesis of fever, and the treatment with galactosamine, simultaneously with the first injection of MDP or endotoxin, would inhibit their synthesis and consequently the development of pyrogenic tolerance. In support of this hypothesis, it has been proposed that a seric component, probably of hepatic origin, neutralizes endotoxin (29,41) and that serum with a high concentration of APP reduces the lethality induced by endotoxin (38). Directly related to the phenomenon investigated in the present study, it has been demonstrated that serum amyloid A, an APP produced by the liver, inhibits fever and hypothalamic production of prostaglandin E 2 induced by cytokines in mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…Beeson (2) and Cooper and Cranston (4) suggested that the tolerance to the pyrogenic effect of endotoxin would result from an increase of its clearance by the reticuloendothelial system resulting in a faster elimination of endotoxin from the circulation. Tolerant animals may also produce a seric component that neutralizes endotoxin, as suggested by Riveau et al (29) and Warren et al (41). However, the aspect that has been most investigated to explain the development of tolerance is the production of the pyrogenic cytokines.…”
mentioning
confidence: 99%
“…Tìm kiếm thuốc kháng nội độc tố Trong nghiên cứu nhiễm trùng gram âm và nhiễm trùng huyết, nội độc tố đóng một vai trò quan trọng trong đáp ứng sinh lý bệnh của vật chủ [24]. Giả định rằng nếu các tác động bất lợi của nội độc tố có thể được loại trừ, khả năng sống trong bệnh nhiễm khuẩn có thể được cải thiện.…”
Section: ứNg Dụng Của Lal Trong Nghiên Cứu Y Dược Họcunclassified
“…In another study we found that sera drawn from rabbits made tolerant to smooth LPS neutralize more heterologous LPS than do normal sera (33). Further investigation has revealed that injection of macrophage supernatants containing interleukin-1 and recombinant interleukin-1 induces increased serum neutralization of LPS (21). In light of these experiments and the controversies surrounding the protective mechanism(s) of passively transferred antisera to gram-negative organisms, we used the limulus inhibition assay to study the amounts of LPS neutralized by rabbit antisera directed to rough and smooth gram-negative organisms.…”
mentioning
confidence: 94%